Analisis Dampak Ekonomi Dari Pengembangan Desa Wisata Jambu Kecamatan Kayenkidul Kabupaten Kediri - Zaki Mustafha; Ziarmal Raqim (Yayasan Gema Bina Nusantara, 2023)
In supporting strategic sectors in Surakarta City, it is necessary to have a link between these sectors, one of which is roads. The road is a means of transportation that connects one place to another. Roads have a fairly important role in the distribution and expedite the wheels of the economy. The road is one of the supporting transportation facilities that is most often used by most people, so it greatly influences people's daily activities. In Law no. 38 of 2004 concerning roads states that roads are transportation infrastructure that play an important role in the economic, social, cultural, environmental, political and defense security fields.